Microvesicles as a potential biomarker of neoplastic diseases and their role in development and progression of neoplasm - Kajdos, Magdalena; Janas, Łukasz; Kolasa-Zwierzchowska, Dorota; R. Wilczyński, Jacek; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2015)
Neoplastic diseases together with cardiovascular diseases are the most frequent causes of death in the Polish population. Cancers of reproductive organs with breast cancer are responsible for the highest morbidity and mortality in women suffering from neoplasm diseases. Asymptomatic dynamics of the development of a neoplasm and no deviations from the normal level of laboratory results contribute to the fact that malignant diseases are diagnosed too late. The aim of modern medicine is to diagnose cancer at the earliest stage, however, there is no sufficiently sensitive and specific biomarker which can be used for diagnostic, prognostic and therapeutic purposes. Cellular interactions play the main role in the development, angiogenesis and invasiveness of a tumor. Recent research suggests the possibility of microvesicles (MVs) involvement in communication between cells. The MVs ability to fuse with various cells is used in cell-to-cell contact. Microvesicles cargo may include growth factors, their receptors, protease, adhesion molecules, signaling molecules and the sequence of DNA, mRNA, and micro-RNA. Larger quantities of MVs released from neoplastic cells affect both the local environment and systematic range causing metastases and progression. The research on molecular mechanisms of MVs’ release and the presence of characteristic oncogenes in blood of patients with neoplasms is being carried out. Confirmation of MVs presence in patients’ serum can potentially serve as useful information for therapeutic purposes and as the biomarker of a neoplastic disease.